Antioxidant Effect of Aqueous Extract of Triticum aestivum Grass on Insulin Resistance models in Wistar Albino Rats - Behera, Jayanti Prava; Ramani, Yerramalli Roja; Prusty, Itishree; Rohit, Sahu Swapna (Free Radicals and Antioxidants)
Context: Prolonged use of hypoglycaemic drugs is problematic due to their toxic side effects and diminution of response. Oral antihyperglycaemic agents from plant sources are therefore being explored for use in traditional medicine. Aims: To study antihyperglycaemic, hypolipidemic and antioxidant effect of aqueous extract of Triticum aestivum grass (TAGE) in two different models of T2DM in wistar albino rats such as High Fat Diet with Low dose STZ and High Fructose Diet models. Settings and Design: Two models of insulin resistance were used (single i.p injection of STZ (45 mg/kg) with high fat diet and fructose 10% w/v, p.o, ad libitum). Methods and Material: STZ with high fat diet and fructose 10% w/v, p.o, in rats was administered for a period of 21 days. Three doses of TAGE (40, 60 and 80 mg/kg, p.o) were used. Pioglitazone (PG) 20 mg/kg was used as the reference standard. At the end of the experimental period, serum biochemical parameters like fasting blood sugar, plasma insulin, lipid profile and MDA and SOD activity were studied in both the models. Statistical analysis used: one way ANOVA followed by Turkey’s multiple comparison test. p<0.05 was considered as significant. Results: In both the models, TAGE significantly lowered plasma glucose, lipid, MDA level and increased SOD activity. It also improved insulin resistance which is comparable to that of normal and standard group. Conclusion: TAGE may be a potent drug, for treatment and prevention of complications of T2DM used alone or in combination with other oral hypoglycaemic agents.
Keywords: Diabetes mellitus; Fructose; Insulin resistance; Streptozotocin; Triticum aestivum